Th1-Dependent Cryptococcus-Associated Immune Reconstitution Inflammatory Syndrome Model With Brain Damage - Khaw, Yee Ming; Aggarwal, Nupur; Barclay, William E.; Kang, Eunjoo; Inoue, Makoto; Shinohara, Mari L. (Frontiers in Immunology, 2020)
Cryptococcus-associated immune reconstitution inflammatory syndrome (C-IRIS) is identified upon immune reconstitution in immunocompromised patients, who have previously contracted an infection of Cryptococcus neoformans (Cn). C-IRIS can be lethal but how the immune system triggers life-threatening outcomes in patients is still poorly understood. Here, we establish a mouse model for C-IRIS with Cn serotype A strain H99, which is highly virulent and the most intensively studied. C-IRIS in mice is induced by the adoptive transfer of CD4+ T cells in immunocompromised Rag1-deficient mice infected with a low inoculum of Cn. The mice with C-IRIS exhibit symptoms which mimic clinical presentations of C-IRIS. This C-IRIS model is Th1-dependent and shows host mortality. This model is characterized with minimal lung inflammation, but infiltration of Th1 cells in the brain. C-IRIS mice also exhibited brain swelling with resemblance to edema and upregulation of aquaporin-4, a critical protein that regulates water flux in the brain in a Th1-dependent fashion. Our C-IRIS model may be used to advance our understanding of the paradoxical inflammatory phenomenon of C-IRIS in the context of neuroinflammation.